Optimal Total Mesorectal Excision for Rectal Cancer: the Role of Robotic Surgery from an Expert's View - Kim, Nam-Kyu (The Korean Society of Coloproctology, 2010)
Total mesorectal excision (TME) has gained worldwide acceptance as a standard surgical technique in the treatment of rectal cancer. Ever since laparoscopic surgery was first applied to TME for rectal cancer, with increasing penetration rates, especially in Asia, an unstable camera platform, the limited mobility of straight laparoscopic instruments, the two-dimensional imaging, and a poor ergonomic position for surgeons have been regarded as limitations. Robotic technology was developed in an attempt to reduce the limitations of laparoscopic surgery. The robotic system has many advantages, including a more ergonomic position, stable camera platform and stereoscopic view, as well as elimination of tremor and subsequent improved dexterity. Current comparison data between robotic and laparoscopic rectal cancer surgery show similar intraoperative results and morbidity, postoperative recovery, and short-term oncologic outcomes. Potential benefits of a robotic system include reduction of surgeon's fatigue during surgery, improved performance and safety for intracorporeal suture, reduction of postoperative complications, sharper and more meticulous dissection, and completion of autonomic nerve preservation techniques. However, the higher cost for a robotic system still remains an obstacle to wide application, and many socioeconomic issues remain to be solved in the future. In addition, we need more concrete evidence regarding the merits for both patients and surgeons, as well as the merits compared to conventional laparoscopic techniques. Therefore, we need large-scale prospective randomized clinical trials to prove the potential benefits of robot TME for the treatment of rectal cancer.